THE EFFECT OF CAPITAL STRUCTURE, SALES GROWTH AND FINANCIAL PERFORMANCE ON COMPANY VALUE (Empirical Study on LQ45 Index Stock Companies for the 2017-2021 Period) - Hari Stiawan; Amellia Putri (Jurnal Ekonomi, 2023)
This study aims to determine the effect of capital structure, sales growth, and financial performance on company value. Company Value is the dependent variable, capital structure, sales growth and financial performance are independent variables. This type of research is quantitative with a population of 45 companies. This research was conducted at LQ45 Stock Index Companies listed on the IDX in 2017-2021, a sample of 21 companies with 5 years of observation, the sample determination method used was purposive sampling. The analytical method uses multiple regression analysis, T test and F test using Eviews 9. The results show that capital structure and financial performance have a positive and significant effect on company value. Sales growth has a negative and significant effect on companyvalue. Meanwhile, capital structure, sales growth and financial performance simultaneous effect on company value.